The presence of clonal cell subpopulations in peripheral blood and bone marrow of patients with refractory cytopenia with multilineage dysplasia but not in patients with refractory anemia may reflect a multistep pathogenesis of myelodysplasia - Cermák, Jaroslav; Belicková, Monika; Krejcová, Hana; Michalová, Kyra; Zilovcová, Sona; Zemanová, Zuzana; Brezinová, Jana; Sieglová, Zuzana (Leukemia research, 2005)
A clonal origin of hematopoiesis was studied by investigation of X-chromosome inactivation patterns (XCIP) in isolated granulocyte, CD14(+) and CD3(+) subpopulations obtained from bone marrow and peripheral blood of 36 female patients with primary myelodysplastic syndrome (MDS). Clonality was assessed by PCR amplification of polymorphic short tandem repeats of the human androgen receptor (HUMARA) gene and by investigation of silent polymorphism of iduronate sulphatase (IDS) or p55 genes. On the basis of results in a control group of 20 healthy age related females, a ratio of at least 9:1 between the two alleles was considered a significant marker of monoclonal hematopoiesis. Ten of the 11 patients with advanced forms of MDS (RAEB, RAEB-T, CMML) had clonal granulocytes and CD14(+) cells in peripheral blood. In patients with early disease, only 2 out of 11 patients (18%) with RA or RARS, according to WHO classification, had clonal granulocytes and CD14(+) cells in peripheral blood and bone marrow and 2 other patients with 5q-syndrome exhibited extremely oligoclonal granulocyte subpopulation in bone marrow. In contrast, we found clonal granulocytes in 12 out of 14 patients (86%) with refractory cytopenia with multilineage dysplasia (RCMD) and 8 of them simultanously exhibited clonal CD14(+) cells. Estimated 3 years survival of patients with early disease and clonal cell subpopulations was 61% as compared with 88% in patients without clonal hematopoiesis. Karyotype abnormalities were detected in 11 of the 25 females with early disease. Clonal patterns were present in 7 out of 8 patients with abberations diagnosed by routine cytogenetics, nevertheless, FISH revealed 5q deletion in 3 patients without signs of clonality in XCIP assay. No correlation was found between the presence of clonal subpopulations and the degree of telomere shortening in early MDS. Despite some limitations, the measurement of XCIP remains a sensitive tool for diagnosis of the first transforming mutation in the clonal development of MDS especially when combined with FISH and when an age related group is used to establish an appropriate allele ratio to exclude constitutional or acquired skewing. The occurrence of clonal cell subpopulations in most of the RCMD patients in contrast to RA may reflect a proposed multistep pathogenesis of MDS with dysplastic changes limited to erythropoiesis in early step and with subsequent development of multilineage dysplasia. The results also support the usefulness of separation of RCMD from 'pure' RA; however, a more complex insight combining different molecular techniques performed in a large number of patients is needed for refined classification of MDS on the basis of new molecular prognostic factors and for indication of more effective targeted therapy.
Keywords: Chromosome Banding; myelodysplastické syndromy; Telomere; telomery; pruhování chromozomů; Myelodysplastic Syndromes; referenční hodnoty; ženské pohlaví; Bone Marrow; Humans; Reference Values; Female; kostní dřeň; refrakterní anemie; hybridizace in situ fluorescenční; In Situ Hybridization, Fluorescence; lidé; Anemia, Refractory